2019
DOI: 10.3390/su11195304
|View full text |Cite
|
Sign up to set email alerts
|

A Seed Coating Delivery System for Bio-Based Biostimulants to Enhance Plant Growth

Abstract: A novel delivery method for the application of bio-based biostimulants as seed coatings was developed using different sources of liquid and powder forms of vermicompost and soy flour. Micronized vermicompost (MVC) and soy flour (SF) were mixed in different combinations as dry seed coating blends and applied using rotary pan seed coating equipment. The physical properties of coated seeds were measured, and as binder concentration increased, coating strength increased. The rates and percentages of germination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…Tyler Co., Cleveland, OH) was utilized to sieve the SF to obtain a particle size smaller than (<75 µ), as previous studies have shown that smaller particle size results in more even distribution of the SF coating on seeds [15]. Seed coating biostimulant materials used in this research were previously analyzed by the Cornell Soil Health Nutrient Analysis Laboratories and recently reported in [27]. (Figure 1).…”
Section: Seed and Coating Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tyler Co., Cleveland, OH) was utilized to sieve the SF to obtain a particle size smaller than (<75 µ), as previous studies have shown that smaller particle size results in more even distribution of the SF coating on seeds [15]. Seed coating biostimulant materials used in this research were previously analyzed by the Cornell Soil Health Nutrient Analysis Laboratories and recently reported in [27]. (Figure 1).…”
Section: Seed and Coating Materialsmentioning
confidence: 99%
“…After the seed coating was completely broken, the force (N) increases until the seed embryo was crushed ( Figure 3). Texture analyzer software (Exponent Connect, version 7.0.2.0, S. Hamilton, MA, USA, 2018) was used to record force for TB and RT [27]. Ten coated seeds were randomly selected from batches of different formulations (SF:DE = 30:70, 40:60, 50:50 and 60:40, SF:MVC-2 (30:70), SF:MVC-3 (30:70), SF:DE:CVE (30:70)) to test their surface compressive strength for both red clover and perennial ryegrass coated seeds.…”
Section: Mechanical Property Testmentioning
confidence: 99%
See 3 more Smart Citations